Resource utilization method of fly ash
Through the microwave heating and centrifugal filtration technology route, fly ash was successfully converted into color-changing silicone, aluminum-ferro-flocculant and sodium chloride snow melting agent, solving the problems of low heat source utilization and low separation efficiency in fly ash resource utilization. , realizes high added value-added full resource utilization, significantly reduces energy consumption and improves separation capacity.
Patent Information
- Application Number
- CN202411282234.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-13
AI Technical Summary
The resource utilization of fly ash in the prior art has problems such as low heat source utilization, high energy consumption and low separation efficiency, resulting in low added value and low economicality in the application of fly ash.
Using the technical route of microwave heating and centrifugal filtration, fly ash is microwave activated by mixing with sodium carbonate and absorbent, and then hydrochloric acid solution is added for ultrasonic centrifugation to obtain color-changing silica gel, aluminum flocculant and sodium chloride snow melting. to achieve full utilization of resources.
It significantly improves the processing capacity of fly ash, reduces energy consumption, shortens the production cycle, maximizes the resource utilization of fly ash, reduces process energy consumption by 90%, improves separation capacity by 99%, and shortens the production cycle to the original 1/6.
Smart Images

Figure BDA0005042009300000171 
Figure BDA0005042009300000172 
Figure BDA0005042009300000173
Abstract
Description
Technical Field
[0001] The invention relates to a method for resource utilization of fly ash, and belongs to the technical field of industrial solid waste application. Background Art
[0002] Fly ash: fine ash collected from the flue gas after the combustion of pulverized coal, which is the main solid waste discharged by coal-fired power plants. It looks similar to cement, with fine but uneven particles, and a color ranging from milky white to gray-black. The surface is loose and porous, with a large specific surface area. The particle size of a single fly ash particle is about 2.5 to 300 μm, and the density is 2 to 2.3 kg / m 3 .
[0003] The main applications of fly ash are: ① manufacturing of building materials such as concrete, bricks, blocks; ② filling projects of infrastructure such as roads, railways, dams, etc.; ③ agricultural fields such as soil remediation and soil conditioning; ④ and graded extraction of valuable metals such as aluminum and silicon, etc. These applications of fly ash have low added value and have special requirements for fly ash, and are not economical.
[0004] The existing technology is relatively simple in the utilization of fly ash, and cannot maximize the resource utilization of fly ash.
[0005] Therefore, in order to effectively utilize fly ash, it is necessary to carry out targeted technical development and optimization of its special chemical composition and mineral structure. In the process of fly ash resource utilization, heat source needs to be provided for activation and heating gel, etc. The heat source provided by the currently developed technology is mainly muffle furnace and water bath heating. These two heat source provision methods have low thermal energy utilization rate and high energy consumption; the separation technology mainly adopts pressure filtration, which has high labor intensity, low separation efficiency and long operation cycle. Based on this, this technology innovatively proposes to use microwave heating and centrifugal filtration from the inside out, which can increase its processing capacity by 665 times.
[0006] Based on the regional advantages and the compounds that need to be added in the fly ash resource process, in line with the principles of full utilization and economy, the present invention proposes to use local high-iron and low-aluminum fly ash as raw material to develop a full utilization technology route for preparing color-changing silica gel and co-producing aluminum-iron flocculant and sodium chloride snow-melting agent. Summary of the invention
[0007] In order to make fuller use of fly ash as a resource, the present invention provides a method for utilizing fly ash as a resource. In the present invention, a color-changing silica gel, an aluminum-iron flocculant and a sodium chloride snow-melting agent can be prepared from fly ash at the same time through a technical route. The specific steps are as follows:
[0008] (1) fly ash, sodium carbonate and a microwave absorber are uniformly mixed and activated by microwave to obtain an activated product;
[0009] (2) adding hydrochloric acid solution to the activated product obtained in step (1) for ultrasonic treatment, centrifugation and filtration, and the filter residue is the absorber, which is recycled;
[0010] (3) subjecting the filtrate of step (2) to microwave heating, and centrifuging after the reaction to obtain a filtrate and a solid;
[0011] (4) adding sodium hydroxide solution to the solid obtained in step (3) to dissolve and adjust the modulus to 3.0-3.5, successively using 2.0 mol / L hydrochloric acid solution to adjust the pH to 7-8, and then using 1.0 mol / L hydrochloric acid solution to adjust the pH to 6-6.5, then pouring the solution into a sieve cup to form silica gel particles, taking out white silica gel particles and soaking them in deionized water at room temperature for aging, then repeatedly soaking and washing with deionized water until the chloride ion concentration is constant, taking out and drying at room temperature until the dry basis moisture content of the silica gel particles is 40%-70%, then soaking in a cobalt chloride solution, separating the solid and liquid, and microwave drying the obtained blue silica gel particles to obtain color-changing silica gel particles;
[0012] (5) adding sodium hydroxide solution to the filtrate obtained in step (3), and stopping the dropwise addition when the pH value of the solution is close to 8.9, and centrifuging to obtain the filtrate and;
[0013] (6) The filtrate obtained by separation in step (5) is evaporated and crystallized to obtain a sodium chloride snow melting agent;
[0014] (7) Add hydrochloric acid solution to the solid obtained in step (5) until the solid is completely dissolved, then add ferric chloride or aluminum chloride to adjust the molar ratio of aluminum to iron to 1:10 to 10:1, then place it in a microwave oven for heating and slowly add 1.0 mol / L sodium hydroxide solution to adjust to a predetermined alkalinity and react for 30 to 180 minutes. After the reaction is completed, cool to room temperature for aging, and then microwave dry to obtain a polyaluminum ferric chloride flocculant.
[0015] Preferably, in step (1), the Fe2O3 content in the fly ash is 3% to 40%, and the Al2O3 content is 10% to 30%; the particle size of the fly ash and sodium carbonate is controlled to be 100 to 400 meshes, and the particle size of the absorber is 50 to 80 meshes.
[0016] Preferably, in step (1), the mass ratio of fly ash to sodium carbonate is 1:0.6 to 1:1.6, the mass ratio of fly ash to absorber is 1:2 to 1:5, and the absorber is one or more of graphite, carbon fiber, and silicon carbide mixed in any proportion.
[0017] Preferably, the microwave activation condition in step (1) is activation at 500-900W microwave for 30-60min.
[0018] Preferably, in step (2), the solid-to-liquid ratio of the activated product to the hydrochloric acid solution is 1:7 to 1:20, expressed in g:mL, and the concentration of the hydrochloric acid solution is 1.5 to 3.5 mol / L.
[0019] Preferably, in step (2), the ultrasonic conditions are 45 to 100 KHz, the power is 240 to 600 W, and the ultrasonic time is 3 to 10 min.
[0020] Preferably, in step (3), the microwave conditions are heating at 500-900W for 30-60min; and the centrifugal conditions are centrifugal separation at 6000-10000rpm for 5-15min.
[0021] Preferably, in step (4), the mesh diameter of the sieve cup is 0.2-8 mm, and an oil cup of No. 0 transformer oil or No. 0 engine oil is provided below the sieve cup; the aging time is 24-48 h, the concentration of the cobalt chloride solution used is 3%-10%, the soaking time in the cobalt chloride solution is 10-24 h, and the microwave drying condition is 500-900 W for 2-6 h.
[0022] Preferably, the concentration of the sodium hydroxide solution in step (5) is 0.1-1.0 mol / L, and the centrifugation condition is 6000-10000 rpm for 5-15 min.
[0023] Preferably, in step (6), the predetermined alkalinity is 0.1-2.0, the aging time is 12-24 hours, and the microwave drying conditions are 500-900W for 2-6 hours.
[0024] Beneficial effects of the present invention
[0025] (1) The present invention utilizes fly ash through a technical route to simultaneously prepare color-changing silica gel, aluminum-iron flocculant and sodium chloride snow-melting agent, thereby maximizing the resource utilization of fly ash.
[0026] (2) The three products developed by the present invention, color-changing silica gel, deicing agent, and polyaluminium ferric chloride flocculant, are basically equivalent to or slightly higher than the requirements of "blue gel indicator, color-changing silica gel and cobalt-free color-changing silica gel HG / T 2765.4-2005, deicing agent GB / T23851-2017, and water treatment agent polyaluminium ferric chloride HG / T 5359-2018", respectively.
[0027] (3) The process energy consumption is reduced by 90%, the separation capacity is increased by 99%, and the production cycle is shortened to 1 / 6 of the original.
[0028] (4) This technical route can change the current situation of fly ash resource utilization with single product and low economic efficiency, and can realize the full utilization of fly ash with high added value. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below by specific implementation methods. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0030] Example 1
[0031] A method for resource utilization of fly ash. In this embodiment, the mass percentage of Fe2O3 in the fly ash used is 33.62%, the mass percentage of Al2O3 is 14.92%, and the mass percentage of SiO2 is 36.64%. The specific steps are as follows:
[0032] (1) 100 g of fly ash with a particle size of 200 mesh, 200 mesh sodium carbonate powder and 50 mesh activated carbon were mixed evenly, placed under 800 W microwave activation for 40 min, and cooled to room temperature to obtain an activated product, wherein the mass ratio of fly ash, sodium carbonate powder and activated carbon was 1:1.2:5.
[0033] (2) Take 215 g of the activated product obtained in step (1) and transfer it to a beaker, place it in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, slowly add 1500 mL of a hydrochloric acid solution with a concentration of 3.14 mol / L, and ultrasonicate for 5 minutes. Centrifuge and separate. The filter residue is the activated carbon absorber, which is recycled.
[0034] (3) The filtrate obtained in the above step (2) was placed in an 800W microwave oven for reaction for 60 minutes. After the reaction was completed, it was centrifuged at 8000 rpm for 10 minutes to obtain a filtrate and a solid.
[0035] (4) 600 mL of 2.0 mol / L sodium hydroxide solution was added to the solid obtained in the above step (3), and the modulus was adjusted to 3.1. The pH was first adjusted to 7 with 2.0 mol / L hydrochloric acid solution, and then the pH was adjusted to 6 with 1.0 mol / L hydrochloric acid solution. The solution was then poured into a 0.5 mm sieve cup (with an oil cup containing No. 0 transformer oil under the sieve cup) to form silica gel particles. The white silica gel particles were taken out and soaked in deionized water for aging at room temperature for 48 h, and then repeatedly soaked and washed with deionized water until the chloride ion concentration was constant. The particles were taken out and placed at room temperature for 24 h to dry naturally, and then transferred to a 3% cobalt chloride solution for soaking for 24 h. The color-changing silica gel particles were taken out and dried in an 800 W microwave oven for 2 h. The color-changing silica gel particles were prepared according to the method of "blue gel indicator, color-changing silica gel and cobalt-free color-changing silica gel (HG / T The moisture absorption rate of the product was 25% when it was kept in a sealed container at RH = 50% and 25 ± 2.5 °C for 48 hours.
[0036] (5) The filtrate obtained in the above step (3) was placed in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, and a 1.0 mol / L sodium hydroxide solution was slowly added dropwise. When the pH of the solution reached 9, the addition was stopped, and the mixture was centrifuged at 8000 rpm for 10 min to obtain a filtrate and a solid.
[0037] (6) The filtrate obtained in step (5) is evaporated and crystallized to obtain a sodium chloride deicing agent. The deicing capacity of the sodium chloride deicing agent is measured according to the measurement method of "Deicing Agent (GB / T23851-2017)". The deicing capacity of the sodium chloride deicing agent at -10±1°C for 30 minutes is 92%.
[0038] (7) The solid obtained by centrifugation in step (5) is transferred to a beaker and placed in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W. A 0.5 mol / L hydrochloric acid solution is added until the solid is completely dissolved, and then 40 g of aluminum chloride hexahydrate is added to adjust the aluminum-iron ratio (molar ratio) to 1.5:1. Subsequently, the mixture is placed in an 800 W microwave oven and heated to a predetermined temperature of 70° C. and 1.0 mol / L sodium hydroxide solution is slowly added dropwise to adjust the alkalinity to a predetermined degree of 1.0 and the reaction is continued for 30 min. After the reaction is completed, the mixture is cooled to room temperature and aged for 24 h. Then, the mixture is placed in an 800 W microwave oven and dried for 4 h to obtain a polyaluminum chloride iron flocculant. The flocculant is used for coal washing wastewater treatment to adjust the wastewater pH to 9. The flocculant dosage is 20 mg·L -1 The mixture was stirred slowly at 100 rpm for 3 min and allowed to settle for 20 min. The COD of the effluent was 48 mg·L -1 The effluent turbidity is 3.5NUT, and the effluent COD and turbidity meet the GB / T19923-2005 standard for reuse in industrial water.
[0039] Polyaluminium ferric chloride performance parameters:
[0040] Mass fraction of Al2O3 / %: 41.65;
[0041] Total Fe mass fraction / %: 4.08;
[0042] Basicity / %: 54.82;
[0043] Mass fraction of insoluble matter / %: 0.30.
[0044] Example 2
[0045] A method for resource utilization of fly ash. The fly ash used in this embodiment has a Fe2O3 content of 27.97%, an Al2O3 content of 15.52%, and a SiO2 content of 38.78%. The specific steps are as follows:
[0046] (1) 100 g of fly ash with a particle size of 300 mesh, 300 mesh sodium carbonate powder and 80 mesh activated carbon were mixed evenly, placed under 800 W microwave activation for 60 min, and cooled to room temperature to obtain an activated product, wherein the mass ratio of fly ash, sodium carbonate powder and activated carbon was 1:1.4:3.
[0047] (2) Take 80 g of the activated product of step (1) and transfer it to a beaker, place it in an ultrasonic instrument with a frequency of 40 kHz and a power of 240 W, slowly add 1600 mL of a 3.4 mol / L hydrochloric acid solution and ultrasonicate for 1 min, centrifuge and separate, the filter residue is the activated carbon absorber, which is recycled.
[0048] (3) The filtrate obtained in the above step (2) was placed in an 800W microwave oven for reaction for 60 minutes. After the reaction was completed, it was centrifuged at 8000 rpm for 10 minutes to obtain a filtrate and a solid.
[0049] (4) 700 mL of 2.0 mol / L sodium hydroxide solution was added to the solid obtained in the above step (3), and the modulus was adjusted to 3.2. The pH was first adjusted to 8 with 2.0 mol / L hydrochloric acid solution, and then the pH was adjusted to 6.5 with 1.0 mol / L hydrochloric acid solution. The solution was then poured into a 0.5 mm sieve cup (with an oil cup containing No. 0 transformer oil under the sieve cup) to form silica gel particles. The white silica gel particles were taken out and soaked in deionized water for aging at room temperature for 48 h, and then repeatedly soaked and washed with deionized water until the chloride ion concentration was constant. The particles were taken out and placed at room temperature for 24 h to dry naturally, and then transferred to a 5% cobalt chloride solution for soaking for 24 h. The color-changing silica gel particles were taken out and dried in an 800 W microwave oven for 2 h. The color-changing silica gel particles were prepared according to the method of "blue gel indicator, color-changing silica gel and cobalt-free color-changing silica gel (HG / T The moisture absorption rate of the product was 26% when it was kept in a sealed container at RH = 50% and 25 ± 2.5 °C for 48 hours.
[0050] (5) The filtrate obtained in the above step (3) was placed in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, and 0.5 mol / L sodium hydroxide solution was slowly added dropwise. When the pH of the solution was close to 9.0, the addition was stopped, and the mixture was centrifuged at 8000 rpm for 10 min to obtain a filtrate and a solid.
[0051] (6) The filtrate obtained in step (5) is evaporated and crystallized to obtain a sodium chloride deicing agent. The deicing capacity of the sodium chloride deicing agent is measured according to the measurement method of "Deicing Agent (GB / T23851-2017)". The deicing capacity of the sodium chloride deicing agent at -10±1°C for 30 minutes is 93%.
[0052] (7) The solid obtained by centrifugation in step (5) is transferred to a beaker and placed in an ultrasonic instrument with a frequency of 40 KHz and a power of 300 W. A 1.0 mol / L hydrochloric acid solution is added until the solid is completely dissolved, and then 60 g of aluminum chloride hexahydrate is added to adjust the aluminum-iron ratio (molar ratio) to 2.5:1. Subsequently, the mixture is placed in an 800 W microwave oven and heated to a predetermined temperature of 70° C. and a 1.0 mol / L sodium hydroxide solution is slowly added dropwise to adjust the alkalinity to a predetermined degree of 1.5 and the reaction is continued for 30 min. After the reaction is completed, the mixture is cooled to room temperature and aged for 24 h. Then, the mixture is placed in an 800 W microwave oven and dried for 4 h to obtain a polyaluminum chloride iron flocculant. The flocculant is used for papermaking white water treatment to adjust the wastewater pH to 8. The flocculant dosage is 25 mg·L -1 The mixture was stirred slowly at 100 rpm for 3 min and allowed to settle for 20 min. The COD of the effluent was 48 mg·L -1 The effluent turbidity is 4.0NUT, and the effluent COD and turbidity meet the GB / T19923-2005 standard for reuse in industrial water.
[0053] Polyaluminium ferric chloride performance parameters:
[0054] Mass fraction of Al2O3 / %: 35.12;
[0055] Total Fe mass fraction / %: 3.08;
[0056] Basicity / %: 41.92;
[0057] Mass fraction of insoluble matter / %: 0.36.
[0058] Example 3
[0059] A method for resource utilization of fly ash. The fly ash used in this embodiment has a Fe2O3 content of 14.37%, an Al2O3 content of 26.05%, and a SiO2 content of 48.08%. The specific steps are as follows:
[0060] (1) 100 g of 200-mesh fly ash, 200-mesh sodium carbonate powder and 65-mesh activated carbon were mixed evenly, activated under 800 W microwave for 60 min, and cooled to room temperature to obtain an activated product, wherein the mass ratio of fly ash, sodium carbonate powder and activated carbon was 1:1.2:3.
[0061] (2) Take 150 g of the activated product of step (1) and transfer it to a beaker, place it in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, slowly add 1500 mL of a hydrochloric acid solution with a concentration of 3.14 mol / L and ultrasonicate for 5 min, centrifuge and separate, the filter residue is the activated carbon absorber, which is recycled.
[0062] (3) The filtrate obtained in the above step (2) was placed in an 800W microwave oven for reaction for 60 minutes. After the reaction was completed, it was centrifuged at 8000 rpm for 15 minutes.
[0063] (4) 600 mL of 2.5 mol / L sodium hydroxide solution was added to the solid obtained in the above step (3), and the modulus was adjusted to 3.1. The pH was adjusted to 7 with 2.0 mol / L hydrochloric acid solution and then adjusted to 6-6.5 with 1.0 mol / L hydrochloric acid solution. The solution was then poured into a 0.3 mm sieve cup (with an oil cup containing No. 0 transformer oil below the sieve cup) to form silica gel particles. The white silica gel particles were taken out and soaked in deionized water for aging at room temperature for 48 h. The white silica gel particles were then repeatedly soaked and washed with deionized water until the chloride ion concentration was constant. The particles were taken out and placed at room temperature for 24 h to dry naturally. The particles were then transferred to a 3% cobalt chloride solution and soaked for 24 h. The particles were taken out and dried in an 800 W microwave oven for 3 h to obtain color-changing silica gel particles. The color-changing silica gel particles were prepared according to the method of "blue gel indicator, color-changing silica gel and cobalt-free color-changing silica gel (HG / T The moisture absorption rate of the product was 23% when it was kept in a sealed container at RH = 50% and 25 ± 2.5 °C for 48 hours.
[0064] (5) The filtrate obtained in the above step (3) was placed in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, and 1.0 mol / L sodium hydroxide solution was slowly added dropwise. When the pH of the solution was close to 8.9, the addition was stopped, and the mixture was centrifuged at 8000 rpm for 10 min to obtain a filtrate and a solid.
[0065] (6) The filtrate obtained in step (5) is evaporated and crystallized to obtain a sodium chloride deicing agent. The deicing capacity of the sodium chloride deicing agent is measured according to the measurement method of "Deicing Agent (GB / T23851-2017)". The deicing capacity of the sodium chloride deicing agent at -10±1°C for 30 minutes is 90%.
[0066] (7) The solid obtained by centrifugation in step (5) is transferred to a beaker and placed in an ultrasonic instrument with a frequency of 40 KHz and a power of 300 W. A 1.0 mol / L hydrochloric acid solution is added until the solid is completely dissolved, and then 80 g of aluminum chloride hexahydrate is added to adjust the aluminum-iron ratio (molar ratio) to 1.5:1. Subsequently, the mixture is placed in an 800 W microwave oven and heated to a predetermined temperature of 80° C. and a 1.0 mol / L sodium hydroxide solution is slowly added dropwise to adjust the alkalinity to a predetermined degree of 1.5 and the reaction is continued for 1 hour. After the reaction is completed, the mixture is cooled to room temperature and aged for 24 hours. Then, the mixture is placed in an 800 W microwave oven and dried for 3 hours to obtain a polyaluminum chloride iron flocculant. The flocculant is used for urban domestic sewage treatment to adjust the wastewater pH to 9. The flocculant dosage is 25 mg·L -1 The mixture was stirred slowly at 100 rpm for 3 min and allowed to settle for 15 min. The COD of the effluent was 48 mg·L-1 The effluent turbidity is 4.3NUT, and the effluent COD and turbidity meet the GB / T19923-2005 standard for reuse in industrial water.
[0067] Polyaluminium ferric chloride performance parameters:
[0068] Mass fraction of Al2O3 / %: 38.28;
[0069] Total Fe mass fraction / %: 3.68;
[0070] Basicity / %: 33.57;
[0071] Mass fraction of insoluble matter / %: 0.23.
[0072] Example 4
[0073] A method for resource utilization of fly ash. The fly ash used in this embodiment has a Fe2O3 content of 6.73%, an Al2O3 content of 26.7%, and a SiO2 content of 50.39%. The specific steps are as follows:
[0074] (1) 100 g of 200-mesh fly ash, 200-mesh sodium carbonate powder and 50-mesh activated carbon were mixed evenly, activated under 800 W microwave for 60 min, and cooled to room temperature to obtain an activated product, wherein the mass ratio of fly ash, sodium carbonate powder and activated carbon was 1:1.2:5.
[0075] (2) Take 100 g of the activated product of step (1) and transfer it to a beaker, place it in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, slowly add 1500 mL of a hydrochloric acid solution with a concentration of 3.14 mol / L and ultrasonicate for 5 min, centrifuge and separate, the filter residue is the activated carbon absorber, which is recycled.
[0076] (3) The filtrate obtained in the above step (2) was placed in an 800W microwave oven for reaction for 60 minutes. After the reaction was completed, it was centrifuged at 8000 rpm for 10 minutes.
[0077] (4) 900 mL of 2.0 mol / L sodium hydroxide solution was added to the solid obtained in the above step (3), and the modulus was adjusted to 3.1. The pH was adjusted to 7.5 with 2.0 mol / L hydrochloric acid solution and then to 6.5 with 1.0 mol / L hydrochloric acid solution. The solution was then poured into a 0.6 mm sieve cup (with an oil cup containing No. 0 transformer oil below the sieve cup) to form silica gel particles. The white silica gel particles were taken out and soaked in deionized water for aging at room temperature for 48 h. The white silica gel particles were then repeatedly soaked and washed with deionized water until the chloride ion concentration was constant. The particles were taken out and placed at room temperature for 24 h to dry naturally. The particles were then transferred to a 3% cobalt chloride solution and soaked for 24 h. The particles were taken out and dried in an 800 W microwave oven for 2 h to obtain color-changing silica gel particles. The color-changing silica gel particles were prepared according to the method of "blue gel indicator, color-changing silica gel and cobalt-free color-changing silica gel (HG / T The moisture absorption rate of the product was 20% when it was kept in a sealed container at RH = 50% and 25 ± 2.5 °C for 48 hours.
[0078] (5) The filtrate obtained in the above step (3) was placed in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, and 1.0 mol / L sodium hydroxide solution was slowly added dropwise. When the pH of the solution was close to 8.9, the addition was stopped, and the mixture was centrifuged at 8000 rpm for 10 min to obtain a filtrate and a solid.
[0079] (6) The filtrate obtained in step (5) is evaporated and crystallized to obtain a sodium chloride deicing agent. The deicing capacity of the sodium chloride deicing agent is measured according to the measurement method of "Deicing Agent (GB / T23851-2017)". The deicing capacity of the sodium chloride deicing agent at -10±1°C for 30 minutes is 93%.
[0080] (7) The solid obtained by centrifugation in step (5) is transferred to a beaker and placed in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W. A 0.5 mol / L hydrochloric acid solution is added until the solid is completely dissolved. Then, the solid is placed in an 800 W microwave oven and heated to a predetermined temperature of 60° C., and a 1.0 mol / L sodium hydroxide solution is slowly added dropwise to adjust the alkalinity to a predetermined degree of 2.0 and the reaction is continued for 60 min. After the reaction is completed, the solid is cooled to room temperature and aged for 24 h. Then, the solid is placed in an 800 W microwave oven and dried for 4 h to obtain a polyaluminium chloride ferric flocculant. The flocculant is used for coal washing wastewater treatment to adjust the wastewater pH to 8. The flocculant dosage is 20 mg·L -1 , slowly stirred at 100 rpm for 5 min, and allowed to settle for 20 min. The COD of the effluent was 45 mg·L -1 The effluent turbidity is 4.5NUT, and the effluent COD and turbidity meet the GB / T19923-2005 standard for reuse in industrial water.
[0081] Polyaluminium ferric chloride performance parameters:
[0082] Mass fraction of Al2O3 / %: 34.21;
[0083] Total Fe mass fraction / %: 2.50;
[0084] Basicity / %: 71.50;
[0085] Mass fraction of insoluble matter / %: 0.32.
[0086] Example 5
[0087] A method for resource utilization of fly ash. The fly ash used in this embodiment has a Fe2O3 content of 3.51%, an Al2O3 content of 28.74%, and a SiO2 content of 54.5%. The specific steps are as follows:
[0088] (1) 100 g of 200-mesh fly ash, 200-mesh sodium carbonate powder and 80-mesh activated carbon were mixed evenly, activated under 800 W microwave for 60 min, and cooled to room temperature to obtain an activated product, wherein the mass ratio of fly ash, sodium carbonate powder and activated carbon was 1:1.2:3.
[0089] (2) Take 125 g of the activated product of step (1) and transfer it to a beaker, place it in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, slowly add 1000 mL of a hydrochloric acid solution with a concentration of 3.40 mol / L, and ultrasonicate for 8 minutes. Centrifuge and separate. The filter residue is the activated carbon absorber, which is recycled.
[0090] (3) The filtrate obtained in the above step (2) was placed in an 800W microwave oven for reaction for 60 minutes. After the reaction was completed, it was centrifuged at 8000 rpm for 15 minutes.
[0091] (4) 1000 mL of 2.0 mol / L sodium hydroxide solution was added to the solid obtained in the above step (3), and the modulus was adjusted to 3.2. The pH was first adjusted to 8 with 2.0 mol / L hydrochloric acid solution, and then adjusted to 6.5 with 1.0 mol / L hydrochloric acid solution. The solution was then poured into a 0.5 mm sieve cup (with an oil cup containing No. 0 transformer oil under the sieve cup) to form silica gel particles. The white silica gel particles were taken out and soaked in deionized water for aging at room temperature for 48 h, and then repeatedly soaked and washed with deionized water until the chloride ion concentration was constant. The particles were taken out and placed at room temperature for 24 h to dry naturally. The particles were then transferred to a 3% cobalt chloride solution and soaked for 24 h. The particles were taken out and dried in an 800 W microwave oven for 2 h to obtain color-changing silica gel particles. The color-changing silica gel particles were prepared according to the method of "blue gel indicator, color-changing silica gel and cobalt-free color-changing silica gel (HG / T The moisture absorption rate of the product was 23% when it was kept in a sealed container at RH = 50% and 25 ± 2.5 °C for 48 hours.
[0092] (5) The filtrate obtained in the above step (3) was placed in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, and 1.0 mol / L sodium hydroxide solution was slowly added dropwise. When the pH of the solution was close to 8.9, the addition was stopped, and the mixture was centrifuged at 8000 rpm for 10 min to obtain a filtrate and a solid.
[0093] (6) The filtrate obtained in step (5) is evaporated and crystallized to obtain a sodium chloride deicing agent. The deicing capacity of the sodium chloride deicing agent is measured according to the measurement method of "Deicing Agent (GB / T23851-2017)". The deicing capacity of the sodium chloride deicing agent at -10±1°C for 30 minutes is 90%.
[0094] (7) The solid obtained by centrifugation in step (5) is transferred to a beaker and placed in an ultrasonic instrument with a frequency of 40KHz and a power of 300W. A 1.0mol / L hydrochloric acid solution is added until the solid is completely dissolved, and then 40g of ferric chloride hexahydrate is added to adjust the aluminum-iron ratio (molar ratio) to 8:1. Subsequently, the mixture is placed in an 800W microwave oven and heated to a predetermined temperature of 80°C and 0.5mol / L sodium hydroxide solution is slowly added dropwise to adjust the alkalinity to a predetermined degree of 1.0 and the reaction is continued for 1h. After the reaction is completed, the mixture is cooled to room temperature and aged for 24h. Then, the mixture is placed in an 800W microwave oven and dried for 4h to obtain a polyaluminum ferric chloride flocculant. The flocculant is used for urban domestic sewage treatment to adjust the wastewater pH to 8. The flocculant dosage is 15mg·L -1 The mixture was stirred slowly at 100 rpm for 3 min and allowed to settle for 25 min. The COD of the effluent was 48 mg·L -1 The effluent turbidity is 4.2NUT, and the effluent COD and turbidity meet the GB / T19923-2005 standard for reuse in industrial water.
[0095] Polyaluminium ferric chloride performance parameters:
[0096] Mass fraction of Al2O3 / %: 34.20;
[0097] Total Fe mass fraction / %: 1.88;
[0098] Basicity / %: 44.64;
[0099] Mass fraction of insoluble matter / %: 0.27.
[0100] Example 6
[0101] A method for resource utilization of fly ash. The fly ash used in this embodiment has a Fe2O3 content of 12.59%, an Al2O3 content of 20.1%, and a SiO2 content of 52.68%. The specific steps are as follows:
[0102] (1) 100 g of 300-mesh fly ash, 300-mesh sodium carbonate powder and 80-mesh activated carbon were mixed evenly, activated under 800 W microwave for 40 min, and cooled to room temperature to obtain an activated product, wherein the mass ratio of fly ash, sodium carbonate powder and activated carbon was 1:1.2:5.
[0103] (2) Take 150 g of the activated product of step (1) and transfer it to a beaker, place it in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, slowly add 1200 mL of a hydrochloric acid solution with a concentration of 3.14 mol / L and ultrasonicate for 5 min, centrifuge and separate, the filter residue is the activated carbon absorber, which is recycled.
[0104] (3) The filtrate obtained in the above step (2) was placed in an 800W microwave oven for reaction for 60 minutes. After the reaction was completed, it was centrifuged at 8000 rpm for 15 minutes.
[0105] (4) 1000 mL of 2.0 mol / L sodium hydroxide solution was added to the solid obtained in the above step (3), and the modulus was adjusted to 3.3. The pH was adjusted to 8 with 2.0 mol / L hydrochloric acid solution and then to a pH range of 6.5 with 1.0 mol / L hydrochloric acid solution. The solution was then poured into a 0.5 mm sieve cup (with an oil cup containing No. 0 transformer oil below the sieve cup) to form silica gel particles. The white silica gel particles were taken out and soaked in deionized water for aging at room temperature for 48 h. The white silica gel particles were then repeatedly soaked and washed with deionized water until the chloride ion concentration was constant. The particles were taken out and placed at room temperature for 24 h to dry naturally. The particles were then transferred to a 3% cobalt chloride solution and soaked for 24 h. The particles were taken out and dried in an 800 W microwave oven for 2 h to obtain color-changing silica gel particles. The color-changing silica gel particles were prepared according to the method of "blue gel indicator, color-changing silica gel and cobalt-free color-changing silica gel (HG / T The moisture absorption rate of the product was 23% when it was kept in a sealed container at RH = 50% and 25 ± 2.5 °C for 48 hours.
[0106] (5) The filtrate obtained in the above step (3) was placed in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, and 1.0 mol / L sodium hydroxide solution was slowly added dropwise. When the pH of the solution was close to 8.9, the addition was stopped, and the mixture was centrifuged at 8000 rpm for 10 min to obtain a filtrate and a solid.
[0107] (6) The filtrate obtained in step (5) is evaporated and crystallized to obtain a sodium chloride deicing agent. The deicing capacity of the sodium chloride deicing agent is measured according to the measurement method of "Deicing Agent (GB / T23851-2017)". The deicing capacity of the sodium chloride deicing agent at -10±1°C for 30 minutes is 95%.
[0108] (7) The solid obtained by centrifugation in step (5) is transferred to a beaker and placed in an ultrasonic instrument with a frequency of 40 KHz and a power of 300 W. A 0.5 mol / L hydrochloric acid solution is added until the solid is completely dissolved. Then, the solid is placed in an 800 W microwave oven and heated to a predetermined temperature of 80° C., and a 1.0 mol / L sodium hydroxide solution is slowly added dropwise to adjust the alkalinity to a predetermined degree of 1.0 and the reaction is continued for 30 min. After the reaction is completed, the solid is cooled to room temperature and aged for 24 h. Then, the solid is placed in an 800 W microwave oven and dried for 4 h to obtain a polyaluminium chloride ferric flocculant. The flocculant is used for papermaking white water treatment to adjust the wastewater pH to 8. The flocculant dosage is 15 mg·L -1 , slowly stirred at 100 rpm for 5 minutes, and after settling for 25 minutes, the COD of the effluent was 54L -1 The effluent turbidity is 5.0NUT, and the effluent COD and turbidity meet the GB / T19923-2005 standard for reuse in industrial water.
[0109] Polyaluminium ferric chloride performance parameters:
[0110] Mass fraction of Al2O3 / %: 32.50;
[0111] Total Fe mass fraction / %: 3.50;
[0112] Basicity / %: 71.50;
[0113] Mass fraction of insoluble matter / %: 0.29.
[0114] Example 7
[0115] A method for resource utilization of fly ash. The fly ash used in this embodiment has a Fe2O3 content of 13.34%, an Al2O3 content of 21.5%, and a SiO2 content of 49.37%. The specific steps are as follows:
[0116] (1) 100 g of 300-mesh fly ash, 300-mesh sodium carbonate powder and 50-mesh activated carbon were mixed evenly, activated under 800 W microwave for 60 min, and cooled to room temperature to obtain an activated product, wherein the mass ratio of fly ash, sodium carbonate powder and activated carbon was 1:1.2:3.
[0117] (2) Take 100 g of the activated product of step (1) and transfer it to a beaker, place it in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, slowly add 800 mL of a hydrochloric acid solution with a concentration of 3.14 mol / L and ultrasonicate for 5 min, centrifuge and separate, the filter residue is the activated carbon absorber, which is recycled.
[0118] (3) The filtrate obtained in the above step (2) was placed in an 800W microwave oven for reaction for 60 minutes. After the reaction was completed, it was centrifuged at 8000 rpm for 10 minutes.
[0119] (4) 900 mL of 2.0 mol / L sodium hydroxide solution was added to the solid obtained in the above step (3), and the modulus was adjusted to 3.2. The pH was first adjusted to 7.5 with 2.0 mol / L hydrochloric acid solution, and then the pH was adjusted to 6 with 1.0 mol / L hydrochloric acid solution. The solution was then poured into a 0.8 mm sieve cup (with an oil cup containing No. 0 transformer oil under the sieve cup) to form silica gel particles. The white silica gel particles were taken out and soaked in deionized water for aging at room temperature for 48 h, and then repeatedly soaked and washed with deionized water until the chloride ion concentration was constant. The particles were taken out and placed at room temperature for 24 h to dry naturally, and then transferred to a 3% cobalt chloride solution for soaking for 24 h. The particles were taken out and dried in an 800 W microwave oven for 2 h to obtain color-changing silica gel particles. The color-changing silica gel particles were prepared according to the method of "blue gel indicator, color-changing silica gel and cobalt-free color-changing silica gel (HG / T The moisture absorption rate of the product was 20% when it was kept in a sealed container at RH = 50% and 25 ± 2.5 °C for 48 hours.
[0120] (5) The filtrate obtained in the above step (3) was placed in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, and 1.0 mol / L sodium hydroxide solution was slowly added dropwise. When the pH of the solution was close to 8.9, the addition was stopped, and the mixture was centrifuged at 8000 rpm for 10 min to obtain a filtrate and a solid.
[0121] (6) The filtrate obtained in step (5) is evaporated and crystallized to obtain a sodium chloride deicing agent. The deicing capacity of the sodium chloride deicing agent is measured according to the measurement method of "Deicing Agent (GB / T23851-2017)". The deicing capacity of the sodium chloride deicing agent at -10±1°C for 30 minutes is 90%.
[0122] (7) The solid obtained by centrifugation in step (5) is transferred to a beaker and placed in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W. A 0.5 mol / L hydrochloric acid solution is added until the solid is completely dissolved. Then, the solid is placed in an 800 W microwave oven and heated to a predetermined temperature of 80° C., and a 1.0 mol / L sodium hydroxide solution is slowly added dropwise to adjust the alkalinity to a predetermined degree of 1.0 and the reaction is continued for 60 min. After the reaction is completed, the solid is cooled to room temperature and aged for 24 h. Then, the solid is placed in an 800 W microwave oven and dried for 4 h to obtain a polyaluminium chloride ferric flocculant. The flocculant is used for coal washing wastewater treatment to adjust the wastewater pH to 9. The flocculant dosage is 15 mg·L -1 , slowly stirred at 100 rpm for 3 min, and allowed to settle for 20 min. The COD of the effluent was 50 mg·L -1 The effluent turbidity is 4.5NUT, and the effluent COD and turbidity meet the GB / T19923-2005 standard for reuse in industrial water.
[0123] Polyaluminium ferric chloride performance parameters:
[0124] Mass fraction of Al2O3 / %: 33.10;
[0125] Total Fe mass fraction / %: 3.50;
[0126] Basicity / %: 71.50;
[0127] Mass fraction of insoluble matter / %: 0.32.
[0128] Example 8
[0129] A method for resource utilization of fly ash. The fly ash used in this embodiment has a Fe2O3 content of 19.61%, an Al2O3 content of 16.15%, and a SiO2 content of 42.63%. The specific steps are as follows:
[0130] (1) 100 g of 200-mesh fly ash, 200-mesh sodium carbonate powder and 50-mesh activated carbon were mixed evenly, activated under 800 W microwave for 60 min, and cooled to room temperature to obtain an activated product, wherein the mass ratio of fly ash, sodium carbonate powder and activated carbon was 1:1.2:5.
[0131] (2) Take 100 g of the activated product of step (1) and transfer it to a beaker, place it in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, slowly add 1000 mL of a 3.4 mol / L hydrochloric acid solution and ultrasonicate for 5 min, centrifuge and separate, the filter residue is the activated carbon absorber, which is recycled.
[0132] (3) The filtrate obtained in the above step (2) was placed in an 800W microwave oven for reaction for 60 minutes. After the reaction was completed, it was centrifuged at 8000 rpm for 10 minutes.
[0133] (4) 800 mL of 2.0 mol / L sodium hydroxide solution was added to the solid obtained in the above step (3), and the modulus was adjusted to 3.2. The pH was first adjusted to 8 with 2.0 mol / L hydrochloric acid solution and then to 6.5 with 1.0 mol / L hydrochloric acid solution. The solution was then poured into a 0.8 mm sieve cup (with an oil cup containing No. 0 transformer oil under the sieve cup) to form silica gel particles. The white silica gel particles were taken out and soaked in deionized water for aging at room temperature for 48 h. The particles were then repeatedly soaked and washed with deionized water until the chloride ion concentration was constant. The particles were taken out and placed at room temperature for 24 h to dry naturally. The particles were then transferred to a 3% cobalt chloride solution and soaked for 24 h. The particles were taken out and dried in an 800 W microwave oven for 2 h to obtain color-changing silica gel particles. The color-changing silica gel particles were prepared according to the method of "blue gel indicator, color-changing silica gel and cobalt-free color-changing silica gel (HG / T The moisture absorption rate of the product was 23% when it was kept in a sealed container at RH = 50% and 25 ± 2.5 °C for 48 hours.
[0134] (5) The filtrate obtained in the above step (3) was placed in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, and a 1.0 mol / L sodium hydroxide solution was slowly added dropwise. When the pH of the solution was close to 9.0, the addition was stopped, and the mixture was centrifuged at 8000 rpm for 10 min to obtain a filtrate and a solid.
[0135] (6) The filtrate obtained in step (5) is evaporated and crystallized to obtain a sodium chloride deicing agent. The deicing capacity of the sodium chloride deicing agent is measured according to the measurement method of "Deicing Agent (GB / T23851-2017)". The deicing capacity of the sodium chloride deicing agent at -10±1°C for 30 minutes is 90%.
[0136] (7) The solid obtained by centrifugation in step (5) is transferred to a beaker and placed in an ultrasonic instrument with a frequency of 40 KHz and a power of 300 W. A 1.0 mol / L hydrochloric acid solution is added until the solid is completely dissolved, and then 20 g of aluminum chloride hexahydrate is added to adjust the aluminum-iron ratio (molar ratio) to 2:1. Subsequently, the mixture is placed in an 800 W microwave oven and heated to a predetermined temperature of 80° C. and a 1.0 mol / L sodium hydroxide solution is slowly added dropwise to adjust the alkalinity to a predetermined degree of 1.0 and the reaction is continued for 1 hour. After the reaction is completed, the mixture is cooled to room temperature and aged for 24 hours. Then, the mixture is placed in an 800 W microwave oven and dried for 4 hours to obtain a polyaluminum chloride iron flocculant. The flocculant is used for papermaking white water treatment to adjust the wastewater pH to 8. The flocculant dosage is 15 mg·L -1 , stirring slowly at 100 rpm for 3 min, and settling for 15 min, the COD of the effluent was 50 mg·L -1 The effluent turbidity is 4.5NUT, and the effluent COD and turbidity meet the GB / T19923-2005 standard for reuse in industrial water.
[0137] Polyaluminium ferric chloride performance parameters:
[0138] Mass fraction of Al2O3 / %: 32.80;
[0139] Total Fe mass fraction / %: 1.56;
[0140] Basicity / %: 64.13;
[0141] Mass fraction of insoluble matter / %: 0.43.
[0142] Example 9
[0143] A method for resource utilization of fly ash. The fly ash used in this embodiment has a Fe2O3 content of 32.3%, an Al2O3 content of 11.6%, and a SiO2 content of 33.8%. The specific steps are as follows:
[0144] (1) 100 g of 300-mesh fly ash, 300-mesh sodium carbonate powder and 80-mesh activated carbon were mixed evenly, activated under 800 W microwave for 60 min, and cooled to room temperature to obtain an activated product, wherein the mass ratio of fly ash, sodium carbonate powder and activated carbon was 1:1.2:3.
[0145] (2) Take 150 g of the activated product of step (1) and transfer it to a beaker, place it in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, slowly add 1500 mL of a 2.0 mol / L hydrochloric acid solution and ultrasonicate for 5 min, centrifuge and separate, the filter residue is the activated carbon absorber, which is recycled.
[0146] (3) The filtrate obtained in the above step (2) was placed in an 800W microwave oven for reaction for 60 minutes. After the reaction was completed, it was centrifuged at 8000 rpm for 10 minutes.
[0147] (4) Add 600 mL of 2.0 mol / L sodium hydroxide solution to the solid obtained in the above step (3), and adjust the modulus to 3.1. First, use 2.0 mol / L hydrochloric acid solution to adjust the pH to 8, and then use 1.0 mol / L hydrochloric acid solution to adjust the pH to 6-6.5. Then pour the solution into a 0.5 mm sieve cup (the sieve cup is equipped with an oil cup containing No. 0 transformer oil) to form silica gel particles. Take out the white silica gel particles and soak them in deionized water at room temperature for aging for 48 hours. Then, soak and wash them repeatedly with deionized water until the chloride ion concentration is constant. Take them out and place them at room temperature for 24 hours to dry naturally. Then, transfer them to a 3% cobalt chloride solution and soak them for 24 hours. Take them out and dry them in an 800 W microwave oven for 2 hours to obtain color-changing silica gel particles. According to the method of "blue gel indicator, color-changing silica gel and cobalt-free color-changing silica gel (HG / T The moisture absorption rate of the product was 20% when it was kept in a sealed container at RH = 50% and 25 ± 2.5 °C for 48 hours.
[0148] (5) The filtrate obtained in the above step (3) was placed in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, and 1.0 mol / L sodium hydroxide solution was slowly added dropwise. When the pH of the solution was close to 8.9, the addition was stopped, and the mixture was centrifuged at 8000 rpm for 10 min to obtain a filtrate and a solid.
[0149] (6) The filtrate obtained in step (5) is evaporated and crystallized to obtain a sodium chloride deicing agent. The deicing capacity of the sodium chloride deicing agent is measured according to the measurement method of "Deicing Agent (GB / T23851-2017)". The deicing capacity of the sodium chloride deicing agent at -10±1°C for 30 minutes is 90%.
[0150] (7) The solid obtained by centrifugation in step (5) is transferred to a beaker and placed in an ultrasonic instrument with a frequency of 40 KHz and a power of 300 W. A 0.5 mol / L hydrochloric acid solution is added until the solid is completely dissolved, and then 70 g of aluminum chloride hexahydrate is added to adjust the aluminum-iron ratio (molar ratio) to 2:1. Subsequently, the mixture is placed in an 800 W microwave oven and heated to a predetermined temperature of 80° C. and 1.0 mol / L sodium hydroxide solution is slowly added dropwise to adjust the alkalinity to a predetermined degree of 1.0 and the reaction is continued for 30 min. After the reaction is completed, the mixture is cooled to room temperature and aged for 24 h. Then, the mixture is placed in an 800 W microwave oven and dried for 4 h to obtain a polyaluminum chloride iron flocculant. The flocculant is used for coal washing wastewater treatment to adjust the wastewater pH to 8. The flocculant dosage is 15 mg·L -1 The mixture was stirred slowly at 100 rpm for 3 min and allowed to settle for 20 min. The COD of the effluent was 48 mg·L -1 The effluent turbidity is 4.3NUT, and the effluent COD and turbidity meet the GB / T19923-2005 standard for reuse in industrial water.
[0151] Polyaluminium ferric chloride performance parameters:
[0152] Mass fraction of Al2O3 / %: 34.87;
[0153] Total Fe mass fraction / %: 2.13;
[0154] Basicity / %: 38.54;
[0155] Mass fraction of insoluble matter / %: 0.45.
[0156] Example 10
[0157] A method for resource utilization of fly ash. The fly ash used in this embodiment has a Fe2O3 content of 35.55%, an Al2O3 content of 15.49%, and a SiO2 content of 6.99%. The specific steps are as follows:
[0158] (1) 100 g of 200-mesh fly ash, 200-mesh sodium carbonate powder and 50-mesh activated carbon were mixed evenly, activated under 800 W microwave for 60 min, and cooled to room temperature to obtain an activated product, wherein the mass ratio of fly ash, sodium carbonate powder and activated carbon was 1:1.2:5.
[0159] (2) Take 100 g of the activated product of step (1) and transfer it to a beaker, place it in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, slowly add 1000 mL of a hydrochloric acid solution with a concentration of 3.14 mol / L and ultrasonicate for 5 min, centrifuge and separate, the filter residue is the activated carbon absorber, which is recycled.
[0160] (3) The filtrate obtained in the above step (2) was placed in an 800W microwave oven for reaction for 60 minutes. After the reaction was completed, it was centrifuged at 8000 rpm for 10 minutes.
[0161] (4) 800 mL of 2.0 mol / L sodium hydroxide solution was added to the solid obtained in the above step (3), and the modulus was adjusted to 3.5. The pH was adjusted to 8 with 2.0 mol / L hydrochloric acid solution and then to 6 with 1.0 mol / L hydrochloric acid solution. The solution was then poured into a 0.8 mm sieve cup (with an oil cup containing No. 0 transformer oil under the sieve cup) to form silica gel particles. The white silica gel particles were taken out and soaked in deionized water for aging at room temperature for 48 h. The white silica gel particles were then repeatedly soaked and washed with deionized water until the chloride ion concentration was constant. The particles were taken out and placed at room temperature for 24 h to dry naturally. The particles were then transferred to a 5% cobalt chloride solution and soaked for 24 h. The particles were taken out and dried in an 800 W microwave oven for 2 h to obtain color-changing silica gel particles. The color-changing silica gel particles were prepared according to the method of "blue gel indicator, color-changing silica gel and cobalt-free color-changing silica gel (HG / T The moisture absorption rate of the product was 23% when it was kept in a sealed container at RH = 50% and 25 ± 2.5 °C for 48 hours.
[0162] (5) The filtrate obtained in the above step (3) was placed in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W, and a 1.0 mol / L sodium hydroxide solution was slowly added dropwise. When the pH of the solution was close to 9.0, the addition was stopped, and the mixture was centrifuged at 8000 rpm for 10 min to obtain a filtrate and a solid.
[0163] (6) The filtrate obtained in step (5) is evaporated and crystallized to obtain a sodium chloride deicing agent. The deicing capacity of the sodium chloride deicing agent is measured according to the measurement method of "Deicing Agent (GB / T23851-2017)". The deicing capacity of the sodium chloride deicing agent at -10±1°C for 30 minutes is 90%.
[0164] (7) The solid obtained by centrifugation in step (5) is transferred to a beaker and placed in an ultrasonic instrument with a frequency of 40 kHz and a power of 300 W. A 1.0 mol / L hydrochloric acid solution is added until the solid is completely dissolved. Then, the solid is placed in an 800 W microwave oven and heated to a predetermined temperature of 90° C., and a 1.0 mol / L sodium hydroxide solution is slowly added dropwise to adjust the alkalinity to a predetermined degree of 1.0 and the reaction is continued for 30 min. After the reaction is completed, the solid is cooled to room temperature and aged for 24 h. Then, the solid is placed in an 800 W microwave oven and dried for 4 h to obtain a polyaluminium chloride ferric flocculant. The flocculant is used for treating coal washing wastewater to adjust the wastewater pH to 9. The flocculant dosage is 20 mg·L -1 , stirring slowly at 100 rpm for 3 min, and settling for 15 min, the COD of the effluent was 50·L -1 The effluent turbidity is 4.0NUT, and the effluent COD and turbidity meet the GB / T19923-2005 standard for reuse in industrial water.
[0165] Polyaluminium ferric chloride performance parameters:
[0166] Mass fraction of Al2O3 / %: 43.63;
[0167] Total Fe mass fraction / %: 2.50;
[0168] Basicity / %: 71.50;
[0169] Mass fraction of insoluble matter / %: 0.24.
[0170] The color-changing silica gel, sodium chloride snow-melting agent and polyaluminium ferric chloride flocculant prepared in Examples 1 and 2 of the present invention are compared with standard products. From the results in Tables 1 to 3, it can be seen that the materials prepared by the present invention are better than the standard products.
[0171] Table 1 Comparison of color-changing silica gel prepared by the present invention and standard
[0172]
[0173] Table 2 Comparison of sodium chloride de-icing agent prepared by the present invention with standard
[0174]
[0175] Table 3 Comparison of the performance of homemade polyaluminium ferric chloride with the standard
[0176]
[0177] The above examples are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above examples, and there may be many variations. For example, high iron and low aluminum fly ash may also be resources with equivalent chemical compositions such as coal gangue, basalt, kaolin, and coal slag. For those skilled in the art, the present application may have various changes and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A method for resource utilization of fly ash, Features: The specific steps are as follows: (1) fly ash, sodium carbonate and a microwave absorber are uniformly mixed and activated by microwave to obtain an activated product; (2) adding hydrochloric acid solution to the activated product obtained in step (1) for ultrasonic treatment, centrifugation and filtration, and the filter residue is the absorber, which is recycled; (3) subjecting the filtrate of step (2) to microwave heating, and centrifuging after the reaction to obtain a filtrate and a solid; (4) adding sodium hydroxide solution to the solid obtained in step (3) to dissolve and adjust the modulus to 3.0-3.5, successively using 2.0 mol / L hydrochloric acid solution to adjust the pH to 7-8, and then using 1.0 mol / L hydrochloric acid solution to adjust the pH to 6-6.5, then pouring the solution into a sieve cup to form silica gel particles, taking out white silica gel particles and soaking them in deionized water at room temperature for aging, then repeatedly soaking and washing with deionized water until the chloride ion concentration is constant, taking out and drying at room temperature until the dry basis moisture content of the silica gel particles is 40%-70%, then soaking in a cobalt chloride solution, separating the solid and liquid, and microwave drying the obtained blue silica gel particles to obtain color-changing silica gel particles; (5) adding sodium hydroxide solution to the filtrate obtained in step (3), stopping the dropwise addition when the pH of the solution is 8.9 to 9, and centrifuging to obtain a filtrate and a solid; (6) The filtrate obtained in step (5) is evaporated and crystallized to obtain a sodium chloride snow-melting agent; (7) Add hydrochloric acid solution to the solid obtained in step (5) until the solid is completely dissolved, then add ferric chloride or aluminum chloride to adjust the molar ratio of aluminum to iron to 1:10 to 10:1, then place it in a microwave oven for heating and slowly add 1.0 mol / L sodium hydroxide solution to adjust to a predetermined alkalinity and react for 30 to 180 minutes. After the reaction is completed, cool to room temperature for aging, and then microwave dry to obtain a polyaluminum ferric chloride flocculant.
2. The method for preparing color-changing silica gel and co-producing aluminum-iron flocculant and sodium chloride snow-melting agent from high-iron and low-aluminum fly ash according to claim 1, Features: Fe in the fly ash in step (1) 2 O 3 The mass percentage of Al is 3% to 40%, 2 O 3 The mass percentage of SiO is 10% to 30%, 2 The mass percentage is 30% to 60%; the particle size of fly ash and sodium carbonate is controlled at 100 to 400 meshes, and the particle size of the absorber is 50 to 80 meshes.
3. The method for preparing color-changing silica gel and co-producing aluminum-iron flocculant and sodium chloride snow-melting agent from high-iron and low-aluminum fly ash according to claim 1, Features: The mass ratio of fly ash, sodium carbonate and absorber in step (1) is 1:1.2:3 to 1:1.4:3, and the absorber is one or more of graphite, carbon fiber and silicon carbide mixed in any proportion.
4. The method for preparing color-changing silica gel and co-producing aluminum-iron flocculant and sodium chloride snow-melting agent from high-iron and low-aluminum fly ash according to claim 1, Features: The microwave activation condition in step (1) is activation at 500-900W microwave for 30-60min.
5. The method for preparing color-changing silica gel and co-producing aluminum-iron flocculant and sodium chloride snow-melting agent from high-iron and low-aluminum fly ash according to claim 1, Features: In step (2), the solid-liquid ratio of the activated product to the hydrochloric acid solution is 1:7 to 1:20, in units of g:mL, and the concentration of the hydrochloric acid solution is 1.5 to 3.5 mol / L.
6. The method for preparing color-changing silica gel and co-producing aluminum-iron flocculant and sodium chloride snow-melting agent from high-iron and low-aluminum fly ash according to claim 1, Features: In step (2), the ultrasonic conditions are 45 to 100 KHz, the power is 240 to 600 W, and the ultrasonic time is 3 to 10 minutes.
7. The method for preparing color-changing silica gel and co-producing aluminum-iron flocculant and sodium chloride snow-melting agent from high-iron and low-aluminum fly ash according to claim 1, Features: In step (3), the microwave conditions are heating at 500-900W for 30-60min; and the centrifugal conditions are centrifugal separation at 6000-10000rpm for 5-15min.
8. The method for preparing color-changing silica gel and co-producing aluminum-iron flocculant and sodium chloride snow-melting agent from high-iron and low-aluminum fly ash according to claim 1, Features: In step (4), the mesh diameter of the sieve cup is 0.2-8 mm, and an oil cup of No. 0 transformer oil or No. 0 engine oil is provided below the sieve cup; the aging time is 24-48 h, the concentration of the cobalt chloride solution used is 3%-10%, the soaking time in the cobalt chloride solution is 10-24 h, and the microwave drying condition is 500-900 W drying for 2-6 h.
9. The method for preparing color-changing silica gel and co-producing aluminum-iron flocculant and sodium chloride snow-melting agent from high-iron and low-aluminum fly ash according to claim 1, Features: The concentration of the sodium hydroxide solution in step (5) is 0.1-1.0 mol / L, and the centrifugal condition is 6000-10000 rpm for 5-15 min.
10. The method for preparing color-changing silica gel and co-producing aluminum-iron flocculant and sodium chloride snow-melting agent from high-iron and low-aluminum fly ash according to claim 1, Features: In step (7), the predetermined alkalinity is 0.1-2.0, the aging time is 12-24 hours, and the microwave drying condition is 500-900W for 2-6 hours.
Citation Information
Patent Citations
Method for extracting high purity alumina and silica gel from coal ash
CN101759210A
Method for preparing coal washing wastewater flocculant by using fly ash and pyrite sintered slag
CN105366777A
Method of recycling aluminum from fly ash
CN108893612A
Method for simultaneously preparing flocculant and snow-melting agent from iron tailings
CN113415863A
Method for fully preparing silicon dioxide and liquid polyaluminum ferric chloride calcium from fly ash
CN113735130A
